Potential DNA binding and nuclease functions of ComEC domains characterized in silico. Issue 10 (1st July 2016) - Baker, James A.; Simkovic, Felix; Taylor, Helen M.C.; Rigden, Daniel J.
ABSTRACT: Bacterial competence, which can be natural or induced, allows the uptake of exogenous double stranded DNA (dsDNA) into a competent bacterium. This process is known as transformation. A multiprotein assembly binds and processes the dsDNA to import one strand and degrade another yet the underlying molecular mechanisms are relatively poorly understood. Here distant relationships of domains in Competence protein EC (ComEC) of Bacillus subtilis (Uniprot: P39695) were characterized. DNA‐protein interactions were investigated in silico by analyzing models for structural conservation, surface electrostatics and structure‐based DNA binding propensity; and by data‐driven macromolecular docking of DNA to models. Our findings suggest that the DUF4131 domain contains a cryptic DNA‐binding OB fold domain and that the β‐lactamase‐like domain is the hitherto cryptic competence nuclease. Proteins 2016; 84:1431–1442. © 2016 The Authors Proteins: Structure, Function, and Bioinformatics Published by Wiley Periodicals, Inc.